A core switching strategy to pyrrolo[2, 3-b]quinolines and diazocino[1, 2-a]indolinones. Issue 38 (6th September 2016) - Jones, Alan M.; Patterson, Stephen; Lorion, Magali M.; Slawin, Alexandra M. Z.; Westwood, Nicholas J.
Abstract : Two novel core-switching rearrangements to natural product-like privileged scaffolds that proceed in up to 99% yield have been developed. Abstract : Two novel core-switching rearrangements to natural product-like privileged scaffolds that proceed in up to 99% yield have been developed. The deviation away from planarity of the central N -acyl urea carbonyl, caused by the structure of the medium-sized ring, dictates the exclusive reaction outcome. Proposed mechanisms and products for the reaction pathways are supported by small molecule X-ray crystallography and an isolated intermediate. Twenty-four novel rearrangement products are reported.